Penerapan 3M dalam Mencegah Penularan COVID-19 Di Bagian Pendaftaran Rawat Jalan BRSUD Tabanan - Putu Chrisdayanti Suada Putri; Luh Yulia Adiningsih; I B Putra Mahardika (Dian Nuswantoro Semarang, 2023)
Background and Objectives: COVID-19 become a global pandemic in 2020. The spread of COVID-19 can occur when there is interaction with someone who has been infected with the virus. Places with a high risk of spreading COVID-19 are referral hospitals for positive COVID-19 patients. Based on this, the researchers identified how the application of 3M to hospital’s staffs, patients and patients' families prevented the transmission of COVID-19 at the outpatient registration section of BRSUD Tabanan and identified factors that influenced these preventive measures.Methods: This study uses a qualitative method. The research location is at BRSUD Tabanan in August-October 2021. The purposive sampling technique is 11 informants. Methods of data collection with interviews and observations to outpatient registration officers, patients, patients’ families who visit. Data validation is done by triangulation method. This research has received ethical approval with the number: 800/0822/Kepeg/BRSUD.Results: hospital’s staffs, patients and patients’ families who come to BRSUD Tabanan have implemented 3M in preventing the transmission of COVID -19 by using masks, washing hands and keeping distance, not crowding, using face shields, hand sanitizer, taking vitamins, maintaining body immunity, implementing a healthy lifestyle and carry out vaccinations. Patients and their families also use hand sanitizers and undergo a screening stage before entering the registration room. Factors that influence 3M actions are maintaining personal safety, the safety of the surrounding environment, and breaking the chain of transmission of COVID-19.Conclusion: The implementation of 3M carried out by officers, patients and their families to prevent the transmission of COVID-19 in the outpatient registration room has been carried out well, namely by using masks, washing hands and maintaining distance.Keywords: Prevention, COVID-19, 3M